Pengaruh pengencer dan lama simpan semen Ayam kampung pada suhu ruang terhadap Motilitas dan viabilitas spermatozoa - Egidius Ulus; Enike Dwi Kusumawati; Aju Tjatur Nugroho Krisnaningsih (Jurnal Sains Peternakan, 2019)
Abstract The study was conducted from February to April 2018 in the field laboratory and integrated laboratory of University Kanjuruhan Malang. The purpose of this research is to know the effect of diluent and timetorage of kampung chicken sperm at room temperature to motility and viability of spermatozoa. The diluent used was NaCl, egg yolk tris aminomethane and no diluent with sperm duration of 0, 3, 6, 9, 12, 15, 18, 21, 24, 27, 30 hours and 10 replications. This research method is experimental laboratory by using completely randomize design of factorial. The data obtained in the study will be analyzed using the method of analysis of variance. The results showed that there was no significant effect (P> 0,05) of diluent, time storage as well as interaction between diluent and time storage to sperm motility and viability. Diluent and time storage which still maintain motility up to the minimum limit for AI was NaCl in 18 hours (41,5%), egg yolk tris aminomethan and without diluent at 12 hours of time storage that was equal to 49% and 42%. While the diluent and the time store that still can maintain viability up to the minimum limit for AI was NaCl and egg yolk tris aminomethan on the 18-hour (82.5%), without diluent on the time storage 12 hours (81.5%). It can be concluded that the optimum spermatozoa motility on NaCl diluent with 6 hours of time storage. While the optimum viability of the NaCl and egg yolk tris aminomethan on the time storage 18 hours.